Peripheral refraction in pseudophakic eyes measured by infrared scanning photoretinoscopy. - Tabernero, J; Ohlendorf, A; Fischer, M; Bruckmann, A; Schiefer, U; Schaeffel, F (2012)
PURPOSE: To obtain quantitative data of peripheral refractive errors in pseudophakic eyes including measurements up to ±45 degrees on the retina. SETTING: University Eye Hospital, Tübingen, Germany. DESIGN: Population-based cross-sectional study. METHODS: Pseudophakic and phakic subjects were measured with a purpose-built scanning photorefractor. The instrument was improved over previous versions. It permits measurement of semicontinuous peripheral profiles over the central 90-degree field of the retina at a faster speed (4 s/scan). RESULTS: Twenty-four pseudophakic and 43 phakic subjects were enrolled. The intraocular lenses (IOLs) induced a mean myopic shift of 2.00 diopters (D) at ±45 degrees of eccentricity in the vertical pupil meridian. Ray-tracing simulations with phakic eye and pseudophakic eye models agreed well with the experimental data. They showed that changes induced by IOLs were a consequence of an increase in astigmatism with eccentricity and a myopic shift in the spherical equivalent. CONCLUSIONS: The peripheral refractions in pseudophakic eyes were more myopic than in phakic eyes as a consequence of the optical design of the IOLs. Whether a more myopic refraction of approximately 2.00 D at 45 degrees has significant effects on visual performance must be tested. Perhaps there is room for improvement in the peripheral optics of IOLs. FINANCIAL DISCLOSURE: No author has a financial or proprietary interest in any material or method mentioned.